Предмет: Алгебра,
автор: alexcros
(3x-7)/6=(2x)/3-(x+4)/2
Ответы
Автор ответа:
0
....................................
Приложения:
Автор ответа:
0
оз. 6
6*(3х-7)/6=6(2х)/3-6(х+4)/2
3х-7=2*2х-3(х+4)
3х-7=4х-3х-12
3х-7=х-12
3х-х=-12+7
2х=-5
х=-2,5
6*(3х-7)/6=6(2х)/3-6(х+4)/2
3х-7=2*2х-3(х+4)
3х-7=4х-3х-12
3х-7=х-12
3х-х=-12+7
2х=-5
х=-2,5
Приложения:
Похожие вопросы
Предмет: История,
автор: arinapoznakova242
Предмет: Математика,
автор: anna74rec25
Предмет: Русский язык,
автор: gulsezimserik0
Предмет: Математика,
автор: djukovska
Предмет: Химия,
автор: 2000ses